Primulina crassirhizoma sp. nov. (Gesneriaceae) from a limestone area along the boundary of Sino-Vietnam (Bangladesh Journal of Plant Taxonomy, 2013)
Primulina crassirhizoma F. Wen, Bo Zhao & Xin Hong, a new species from a limestone area along the boundary of Sino-Vietnam, is described and illustrated. It is similar to P. linearifolia and P. longgangensis in leaf and flower shape, but can be distinguished by extremely strong rhozime, with conspicuous internodes, leaf blade adaxial surface nitid, sparsely appressed strigose, lateral veins 68 on each side of midrib, calyx narrowly triangular to narrowly ovate, corolla pale purple to bluish purple, c. 3.5 cm long, tubenearly tubular, adaxial lip c. 6 mm, abaxial lip 8-9 mm, glabrous anthers and staminodes 3.DOI: http://dx.doi.org/10.3329/bjpt.v20i2.17387Bangladesh J. Plant Taxon. 20(2):129-134, 2013